Kinetics and equilibrium studies of phosphate removal from aqueous solution by calcium silicate hydrate synthesized from electrolytic manganese residue - Changxin Li; Yuan Yu; Qiuyue Li; Hong Zhong; Shuai Wang (Adsorption Science & Technology)
The calcium silicate hydrate synthesized from electrolytic manganese residue was investigated as adsorbents to remove the phosphate from aqueous solutions. The effects of different experimental parameters, including contact time, initial phosphate concentration, solution pH, and temperature on the phosphate adsorption were investigated. The results showed that the phosphate adsorption was highly pH-dependent, with removal being more efficient under the pH range of 10.0–11.0. The Freundlich and Langmuir models were used to simulate the sorption equilibrium, and the results indicate that the adsorption data fitted well to the Langmuir model with which the maximum phosphate adsorption capacity was estimated to be 65.79–85.47 mg/g at 25–35°C. Meanwhile, the kinetic data confirmed that the sorption of phosphorus onto electrolytic manganese residue–calcium silicate hydrate can be best described by the pseudo-second-order kinetic model, suggesting that the adsorption process might be chemical sorption. Furthermore, thermodynamic studies illustrated that the adsorption process was endothermic and spontaneous in nature.